Peningkatan Perekonomian Masyarakat Melalui Pelatihan Pembuatan Hidroponik Vertikal - Fadhli, Khotim; Mahendri, Wisnu; Yuliana, Anggi Indah; Kartika, Defi; Azizah, Azizah; Widyaningsih, Bekti; Ulfa, Maria; Izzudin, M. Husam; Khudzefi, Azam (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2025)
This community service activity is focused on socializing and training village residents in creating a vertical hydroponic system as a means of improving economic conditions in Ketapang Kuning village. This initiative addresses the problem of limited land and agricultural resources, which hinder local economic development. The main aim is to improve the economy through the introduction of innovative and land-saving agricultural techniques, namely vertical hydroponics, which are expected to provide a sustainable source of income and increase food security for the community. This approach involves holding workshops and hands-on training sessions to educate village residents about the principles and practices of vertical hydroponics. In this community service activity, the team from Unwaha trained village residents, especially PKK women, about vertical hydroponics using the Participatory Action Research (PAR) method, which allows participants to create their own hydroponic systems with guidance from experts. The results show an increase in the understanding of participants who are housewives from Ketapangkuning village regarding how to make vertical hydroponics in a simple way. Apart from that, participants also increasingly understand the importance of the role of housewives in improving the family's economic level through alternative sources of income.  During the mentoring period, participants have also succeeded in implementing a hydroponic system in their homes. This initiative not only meets immediate economic needs but also empowers communities with skills and knowledge for long-term independence.